Antiviral Activities of Officinaloside C against Herpes Simplex Virus-1 - Ji Xiao; Miaomiao Cai; Yifei Wang; Ping Ding (Molecules, 2022)
The iridoid compounds in traditional Chinese medicine play a prominent role in their antiviral effects. We previously reported the anti-inflammatory effect of new iridoids from the aerial parts of Morinda officinalis. Nevertheless, several open questions remain to explore the other biological functions of these new iridoid compounds. Herpes simplex virus-1 (HSV-1) is one of the most prevalent pathogens in human beings worldwide and due to limited therapies, mainly with the guanosine analog aciclovir (ACV) and other analogs, the search for new drugs with different modes of action and low toxicity becomes particularly urgent for public health. This study aimed to explore the anti-HSV-1 effects of iridoids from the aerial parts of Morinda officinalis. The dried aerial parts of Morinda officinalis were extracted with 95% ethanol and systematic separation and purification were then carried out by modern column chromatography methods such as silica gel column, RP-ODS column, Sephadex LH-20 gel column, and semi-preparative liquid phase, and the structure of these compounds were identified through the physical and chemical properties and a variety of spectral techniques. The obtained seven new iridoid compounds were screened for antiviral activity on HSV-1 through CCK8 and the cytopathic effect, and then the plaque reduction assay, the anti-fluorescence reporter virus strain replication, and RT-qPCR experiments were carried out to further evaluate the antiviral effect. Seven new iridoid compounds (officinaloside A–G) were identified from the aerial parts of Morinda officinalis, and officinaloside C showed anti-HSV-1 activity. Further functional experiments confirmed that officinaloside C has a significant inhibiting effect on HSV-1 virus plaque formation, viral gene, and protein expression, and fluorescent virus replication. Our findings suggest that officinaloside C has significant inhibitory effects on viral plaque formation, genome replication, and viral protein expression of HSV-1 which implies that officinaloside C exhibits viral activity and may be a promising treatment for HSV-1 infection.